Campur Kode dalam Lirik Lagu Twilight Karya King Gnu - Muharrom Al Hakim, Mohammad Syahrul; Hermawan, Gede Satya (KIRYOKU, 2025)
In the lyrics of the song Twilight by Tsuneta from the band King Gnu, the use of code mixing is found. This discussion aims to discuss the use of code mixing in Japanese song lyrics. The selection of the song Twilight is due to the presence of a code-mixed lyric that carries the meaning of the whole song. This is interesting to discuss. By using qualitative descriptive methods as an analysis method and the listen and note technique as a data collection method. Data sources were obtained from Spotify and the official King Gnu YouTube channel—secondary data in the form of King Gnu's interview results with Billboard Japan. The study's results revealed five alternations and two insertions. In the alternation, the use of the final particle 'yo' and the use of the conditional form -nara as a transition marker were found. In the insertion, the use of the genitive case marker 'no' was found as an adhesive between the Japanese constituent and the English constituent. The repetition of the noun twilight shows that the English noun had a role in forming the meaning of the song. The reason for using English is to strengthen the meaning and form rhymes in the song lyrics.